The Response of Plants and Mycorrhizal Fungi to Nutritionally-Heterogeneous Environments Are Regulated by Nutrient Types and Plant Functional Groups - Liu, Bitao; Han, Fei; Xing, Kaixiong; Zhang, Aiping; Rengel, Zed (Frontiers in Plant Science, 2021)
Nutrient type and plant functional group are both important in influencing proliferation of roots or hyphae and their benefit to plant growth in nutritionally heterogeneous environments. However, the studies quantifying relative importance of roots vs. hyphae affecting the plant response to nutrient heterogeneity are lacking. Here, we used meta-analysis based on 791 observations from 56 published studies to evaluate response patterns of seven variables related to growth and morphological traits of plants and mycorrhizal fungi in nutritionally heterogeneous environments. We found that phosphorus [P] and organic fertilizer [OF] supply significantly increased shoot (+18.1% and +25.9%, respectively) and root biomass (+31.1% and +23.0%, respectively) and root foraging precision (+11.8% and +20.4%, respectively). However, there was no significant difference among functional groups of herbs (grasses, forbs and legumes), between herbs and woody species, and between arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) tree species in the shoot, root and mycorrhizal fungi responses to nutrient heterogeneity, except for root biomass and root foraging precision among grasses, forbs and legumes, and mycorrhizal hyphal foraging precision between AM and ECM tree species. Root diameter was uncorrelated with neither root foraging precision nor mycorrhizal hyphal foraging precision, regardless of mycorrhizal type or nutrient type. These results suggest that plant growth and foraging strategies are mainly influenced by nutrient type, among other factors including plant functional type and mycorrhizal type.